Negative correlation between ACE2 gene expression levels and loss of taste in a cohort of COVID-19 hospitalized patients: New clues to long-term cognitive disorders - Braga-Paz, Isabela; Ferreira de Araújo, João Locke; Alves, Hugo José; de Ávila, Renata Eliane; Resende, Gustavo Gomes; Teixeira, Mauro Martins; de Aguiar, Renato Santana; de Souza, Renan Pedra; Bahia, Diana (Frontiers in Cellular and Infection Microbiology, 2022)
In early 2020, one of the most prevalent symptoms of SARS-CoV-2 infection was the loss of smell (anosmia), found in 60-70% of all cases. Anosmia used to occur early, concomitantly with other symptoms, and often persisted after recovery for an extended period, sometimes for months. In addition to smell disturbance, COVID-19 has also been associated with loss of taste (ageusia). The latest research suggests that SARS-CoV-2 could spread from the respiratory system to the brain through receptors in sustentacular cells localized to the olfactory epithelium. The virus invades human cells via the obligatory receptor, angiotensin-converting enzyme II (ACE2), and a priming protease, TMPRSS2, facilitating viral penetration. There is an abundant expression of both ACE2 and TMPRSS2 in sustentacular cells. In this study, we evaluated 102 COVID-19 hospitalized patients, of which 17.60% presented anosmia and 9.80% ageusia. ACE1, ACE2, and TMPRSS2 gene expression levels in nasopharyngeal tissue were obtained by RT-qPCR and measured using ΔCT analysis. ACE1 Alu287bp association was also evaluated. Logistic regression models were generated to estimate the effects of variables on ageusia and anosmia Association of ACE2 expression levels with ageusia. was observed (OR: 1.35; 95% CI: 1.098-1.775); however, no association was observed between TMPRSS2 and ACE1 expression levels and ageusia. No association was observed among the three genes and anosmia, and the Alu287bp polymorphism was not associated with any of the outcomes. Lastly, we discuss whetherthere is a bridge linking these initial symptoms, including molecular factors, to long-term COVID-19 health consequences such as cognitive dysfunctions.